Edible Oils Consumption and the Fatty Acids Profile of the Most Common Consumed Brands in Shiraz, Iran - Erfaneh Aalipanah1, 2, Enayat Berizi1 , Anoush Khamoushi1, 2, Morteza Zare1 , Zahra Sohrabi1 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Aim: This study aimed to measure edible oils consumption, the most preferred brands and their fatty acidprofile compared with standard values in Shiraz, Iran.Methods: In this cross-sectional study 384 households were assessed. Edible oil types (frying, sunflower,corn, canola, rapeseed, mixed, solid, olive, grapeseed, sesame, and animal), brands, volume of consumed,attention to the label, and changes in the volume of oil consumption compared to the last year were measured.Resistance, fatty acid patterns, total trans fatty acid, smoke point, and saturated fatty acids of the three mostfrequently consumed edible oils were compared to the standard recommended values.Findings: The mean of households? oil consumption was 40.34 ± 32.88 kg per year. Frying (78.6%),sunflower (60.70%), and olive (37.5%) oils were the most common consumed oil. 57.6% of participants readthe labels. 28.9% could not understand the labels information. Compare to the last year, 53.8%, 46.8%, and55.5% of studied households reported decrease in the liquid, solid and frying oils consumption. Fatty acidprofile in majority of studied brands were in the standard range. Myristic acid level in the three major brandsof solid oil was out of the standard range. The level of C16:1, C18:1, C18:2, C18:3 in the third commonolive oil, C14:0 and saturated fatty acid in the third common frying oil were out of the standard range. Theresistance level in the third common corn oil, the first common and the third common frying oil was out ofthe standard range.Conclusion: Liquid, solid and frying oils consumption among studied population decrease than the lastyear, which can be helpful to reduce the risk of chronic diseases. The fatty acids profiles of the most commonconsumed brands were in the standard range.